(untitled) (Swiss Medical Weekly, 2016)
BACKGROUND: Trastuzumab (Herceptin®, Roche) has significantly improved the prognosis of patients with HER2-positive metastatic breast cancer. Some patients remain in remission for many years. However, there are no prognostic markers associated with long-term survival. This study aimed to analyse treatment patterns of HER2-positive metastatic breast cancer at a single institution and explore prognostic factors for long-term survival after HER2-targeted treatment. PATIENTS AND METHODS: This was a retrospective cohort study of all patients with HER2-positive metastatic breast cancer receiving first-line treatment with HER2-targeted therapy between 2004 and 2014 at the University Hospital of Zurich (n = 81). Overall survival (OS) and other time-to-event endpoints were determined with Kaplan-Meier curves and clinicopathological factors predicting long-term outcome were identified by use of the log-rank test. RESULTS: The median OS for the cohort was 5.9 years (95% confidence interval [CI] 3.5–8.3). Twenty patients (28.6%) remained in complete remission after 1 year, 11 (15.7%) after 2 years and 4 (5.7%) beyond 5 years. The median progression-free survival was 13.6 months (95% CI 9.0–18.3). The objective response rate (ORR) was 60.5% with 16 (19.8%) complete responses and 33 (40.8%) partial responses. Six (7.4%) patients had brain metastases as first site of relapse and they had a median OS of 1.9 years (95% CI 1.7–2.2 years). Thirty-four of all 81 patients (42%) had developed brain metastases by the time of death or last follow-up. Median OS after diagnosis of brain metastases was 26 months (95% CI 19.9–32.0). Only primary brain metastases were found to be a prognostic marker associated with shorter overall survival. Hormone-receptor status and presence of visceral metastases at primary diagnosis were not associated with prognosis. Only four patients (4.9%) developed some degree of left ventricular dysfunction under treatment with trastuzumab. CONCLUSIONS: HER2-targeted treatment has improved the overall survival of patients with HER2-postive metastatic breast cancer with median OS exceeding 5 years. There are, however, no predictive markers for a long-term survival. Only the absence of primary brain metastases seems to be an indicator of a good prognosis. Clinical trial number: SNCTP000001431